2018
DOI: 10.3389/fpubh.2018.00095
|View full text |Cite
|
Sign up to set email alerts
|

Severe Urban Outdoor Air Pollution and Children’s Structural and Functional Brain Development, From Evidence to Precautionary Strategic Action

Amedeo D’Angiulli

Abstract: According to the latest estimates, about 2 billion children around the world are exposed to severe urban outdoor air pollution. Transdisciplinary, multi-method findings from epidemiology, developmental neuroscience, psychology, and pediatrics, show detrimental outcomes associated with pre- and postnatal exposure are found at all ages. Affected brain-related functions include perceptual and sensory information processing, intellectual and cognitive development, memory and executive functions, emotion and self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 46 publications
2
22
0
3
Order By: Relevance
“…These findings showing associations between air pollution and total gray-matter and total white-matter volumes are consistent with previous studies that found associations between exposure to air pollution and brain changes [1,5,11]. Specifically, a study of older women from the Women's Health Initiative Memory Study (WHIMS; age range 71 to 89 years; N = 1403) found that PM 2.5 was associated with reduced white-matter volume and total brain volume but not gray-matter volume [10].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings showing associations between air pollution and total gray-matter and total white-matter volumes are consistent with previous studies that found associations between exposure to air pollution and brain changes [1,5,11]. Specifically, a study of older women from the Women's Health Initiative Memory Study (WHIMS; age range 71 to 89 years; N = 1403) found that PM 2.5 was associated with reduced white-matter volume and total brain volume but not gray-matter volume [10].…”
Section: Discussionsupporting
confidence: 93%
“…Much of the world's population is exposed to air pollution [1]. In fact, the World Health Organization estimated that in 2016, 91 percent of people across the world lived where exposure to air pollution exceeded their published standards [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these findings, compared to our understanding of how PM2.5 affects cardiorespiratory functioning and physical health, we still know far less about the impact of PM2.5 on pediatric brain development in humans, especially beyond early childhood (5).…”
mentioning
confidence: 99%
“…Particulate matter 2.5 (PM2.5), or air particles smaller than 2.5 µm in diameter, may be especially dangerous. PM2.5 particles can be composed of harmful mixtures of metals and chemicals that are easily inhaled deeply into the lungs and absorbed into the bloodstream, leading to local and systemic inflammation and oxidative stress (2) which, in turn, can adversely affect brain development (5). Smaller PM2.5 particles can also reach the brain, potentially contributing to neuroinflammation and brain damage.…”
mentioning
confidence: 99%